2023
DOI: 10.4239/wjd.v14.i3.198
|View full text |Cite
|
Sign up to set email alerts
|

Multiple influences of the COVID-19 pandemic on children with diabetes: Changes in epidemiology, metabolic control and medical care

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has heavily affected health worldwide, with the various forms of diabetes in children experiencing changes at various levels, including epidemiology, diabetic ketoacidosis rates and medical care. Type 1 diabetes showed an apparent increase in incidence, possibly owing to a direct damage of the virus to the β-cell. Diabetic ketoacidosis also increased in association with the general fear of referring patients to the hospital. Most children with diabetes (both typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…It was a peak time of COVID-19 pandemic, which offered great difficulties in consulting and taking patient's records of the disease, and also negatively affected the overall situation at PDCs. The studies showed that COVID-19 pandemic have affected the diabetic patients more severely in different parts of the world [30][31][32][33]. Furthermore, we investigated T1DM issue among children in unprivileged areas of Punjab, Pakistan, where medical facilities of acceptable quality are not readily available for general public.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was a peak time of COVID-19 pandemic, which offered great difficulties in consulting and taking patient's records of the disease, and also negatively affected the overall situation at PDCs. The studies showed that COVID-19 pandemic have affected the diabetic patients more severely in different parts of the world [30][31][32][33]. Furthermore, we investigated T1DM issue among children in unprivileged areas of Punjab, Pakistan, where medical facilities of acceptable quality are not readily available for general public.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is also known that among children at the age of 20 and less, boys and girls are equally affected [14,16]. There are reports that the incidence has increased due to COVID-19 pandemic in Germany [30], UK [31], Romania [32] and Italy [33].…”
Section: Introductionmentioning
confidence: 99%
“…The association between COVID-19 infection and type 1 diabetes (T1D) in children has been extensively studied in the last three years. However, the available data regarding the trend of incidence of newly diagnosed T1D during the COVID-19 pandemic are conflicting [ 87 , 88 ].…”
Section: Diabetesmentioning
confidence: 99%